Characteristics of moral distress from nurses' perspectives: An integrative review - Mohannad Aljabery; Isabel Coetzee-Prinsloo; Annatjie van der Wath; Nathira Al-Hmaimat (Elsevier, 2024)
Objective: This integrative review aimed to identify the common characteristics of moral distress in nursing and distinguish it from other types of distress by examining nurses' perspectives in the literature. These insights will help update existing tools and create new ones to capture moral distress better, guiding the development and implementation of strategies to support nurses in addressing this challenge. Methods: Whittemore and Knafl's integrative review method was employed to guide a systematic search for literature in three databases (EBSCO Medline, CINAHL, and PubMed). Additionally, two journals, Bioethics and Nursing Ethics, were manually searched to reduce search bias. The included studies were primary resources published in English between 2018 and 2023, utilizing quantitative, qualitative, or mixed methods to examine moral distress's characteristics, components, and definitions. All of identified studies were screened, extracted, and analyzed independently by two researchers. Results: Nineteen studies were included. The results were grouped into five themes shaping the main characteristics of moral distress: 1) experiencing a moral situation, with five ethically conflicted situations identified, including treatment plans, professional and personal moral values, team dynamics, complex contexts, clinical practices, and patient-centered care; 2) making a moral judgment, where nurses experience moral distress when they cannot act consistently with their values, ethical principles, and moral duties; 3) the presence of constraints, categorized at three levels: individual factors related to the nurse, patient, and patient's family; team factors related to the team or unit involved; and system factors, including institutional and policy elements; 4) moral wrongdoing, which occurs when nurses are unable to perform the right moral action; and 5) moral suffering, with studies showing that moral distress impacts physical, emotional, and psychological well-being. Conclusion: The findings enhance the understanding of moral distress characteristics among nursing staff, highlighting the concept of the crescendo effect, which underscores the cumulative and escalating nature of unresolved moral distress, emphasizing the need to address moral conflicts proactively to prevent the erosion of moral integrity and professional satisfaction.